High-pressure processing: Effect on textural properties of food- A review. (August 2023) - Gokul Nath, K.; Pandiselvam, R.; Sunil, C.K.
Abstract: The increasing consumer trends for zero to minimally-processed safe foods have boosted the trend of non-thermal processing technologies. The adaptation of non-thermal pre-processing and processing methodologies has proven to be very efficient in extending shelf life and enhancing product quality and safety. High-pressure processing (HPP) is a non-thermal, chemical residue-free processing method which involves the application of increased pressure on the products to achieve shelf-stable products by microbial and enzymatic inactivation with minimal impact on the nutritional and chemical composition of foods. The foods used for HPP are meat and meat products, fruits and vegetables, dairy products, nuts and seeds, eggs, and other highly perishable products or minimally processed products. The use of high pressure on the products can critically alter the textural properties such as firmness, hardness, cohesiveness and others. The texture is a very important organoleptic property, which can decide the consumer acceptance of the foods. HPP has proven to improve textural attributes in various food products with minimal deterioration. This review critically discusses the impact of HPP on the textural changes in different food matrices. Graphical abstract: Image 1 Highlights: HPP critically alters the texture of food with minimal impact on nutritional and chemical composition of foods. HPP alters the texture by modification of structural components such a protein, and inactivation/activate enzyme activity. Texture modification helps to create food products with improved properties and desired functionality. HPP combined with other technologies has significant impact on texture.